Extrato bruto de Hymenaea courbaril L. apresenta efeito antinociceptivo em modelos de dor em camundongos - Severo, Gabriela De Campos (2016)
Hymenaea courbaril L. (Fabaceae), popularly known in Brazil as "Jatoba" is a tropical species of South America. Hymenaea genus is commonly used in Brazilian traditional medicine for the treatment of inflammation, bacterial infections, rheumatism and anemia. This study investigated the antinociceptive effect of crude extract from the bark of H. courbaril stem in a model of rheumatoid arthriris in mice. For this, adult male Swiss mice were used (most experimental protocols) and female (acute toxicity test) (25-30 g). First, we evaluate the antinociceptive effect of the crude extract of H. courbaril (HccE, 100 mg/kg, p.o.) and its fractions ethyl acetate (Eta, 100 mg/kg, p.o.) chloroform (Chlo, 100 mg/kg, p.o.), and butanol (But 100 mg/kg, p.o.) in the capsaicin test. Rheumatoid arthritis was induced by administration of complete Freund’s adjuvant (CFA; Mycobacterium tuberculosis, 1 mg/ml; 20 ul/paw) into the plantar surface of the right hind paw of the animal. To evaluate the antinociceptive effect of HccE in the rheumatoid arthritis model (10-100 mg/kg, p.o.), von Frey test was used. The opioid antagonist naloxone receptor (2 mg/kg, i.p.) was used to investigate the possible involvement of opioid system in the antinociceptive effect of HccE. To avaluate the thermal nociceptive activity of HccE was performed the tail immersion test (tail-flick). They were also performed testing locomotor activity, gastric lesion, gastrointestinal transit, body temperature, to evaluate the possible adverse effects of treatment with HccE, as well as tests to assess toxicity. The HccE (100 mg/kg, p.o.), Chlo and But fractions (100 mg/kg, p.o.) caused antinociceptive effect in the capsaicin test. HccE (10-100 mg/kg, p.o.) caused antinociception in the CFA-induced rheumatoid arthritis model, and naloxone did not prevent this effect. In the tail-flick test, HccE (100 mg/kg p.o.) increased the tail withdrawal latency at 1, 4 and 6 h. The HccE (100 mg/kg, p.o.) neither alter locomotor activity, gastrointestinal function, and body temperature nor developed gastric lesions. These results demonstrate that H. courbaril has analgesic effect in an arthritic pain model confirming its use in folk medicine without causing adverse effects.